Physiological indicators in screening of winter wheat gene fund for breeding on yielding and adaptability - Yessimbekova, M. А.; Mukin, K. B. (International Journal of Biology and Chemistry, 2014)
The perspective high yielding of winter bread wheat germplasm is differentiated by genetic systems of adaptability, attraction and plasticity micro-distributions of the traits «mass of kernel per ear» and «mass of chaff per ear». The donors of the specified traits limiting yielding of winter bread wheat are selected.